POTENSI EKONOMI SUMBERDAYA MANGROVE UNTUK KESEJAHTERAAN MASYARAKAT KAMPUNG BERANGBANG (SUATU KASUS DI DESA LONTAR KECAMATAN TIRTAYASA KABUPATEN SERANG) - Ratu Rosmiyati; Aris Supriyo Wibowo; Khaerul Saleh (JURNAL AGRIBISNIS TERPADU, 2022)
This research was conducted in the Berangbang Lontar Village, Tirtayasa District, Serang Regency which aims to know the potential benefits of mangroves and the value of direct benefits and the value of indirect benefits of rainbow bridge mangrove forests. The analysis used is Economic Valuation direct benefits and indirect benefits and willingness to pay the public. The methods used in this study were questionnaires and interviews. The data used is primary data and secondary data. The type of sampling is Accidental Sampling. The results of the study showed that the direct benefits obtained by the community from mangrove forests in the research area are fish, crabs, shrimp and seaweed with an economic value of Rp 928,000 with an average value per ha of Rp 4,640. The value of indirect benefits consists of tourism value with an economic value of Rp 11,900,000 with an average value per ha of Rp 59,500. The value of the option benefits is 227,820 per ha. The result is multiplied by the total area of mangrove forest ecosystems along lontar village which is an area of 200 ha, with the total value of biodiversity benefits of Rp 45,564,000 per year. The value of existence benefits is Rp 1,606.1 ha /year with a mangrove area of 200 ha. Therefore, the total number of benefits of mangrove forest ecosystem in Berangbang village is Rp 321,220/year. The total economic benefit value of mangroves in Berangbang village is Rp 71,240,800 while the total benefit value per ha is Rp 598,172 per year.